Performance study of a wireless mobile ad hoc network with orientation-dependent internode communication scheme - Kostin, Alexander; Oz, Gurcu; Haci, Huseyin (Wiley, 2014)
A Petri-net-based simulation model of a wireless mobile ad hoc network is developed and studied. The model covers all the fundamental aspects of behaviour of such a network and uses a novel scheme of orientation-dependent (or sector-dependent) internode communication, with random states of links. The proposed scheme enables representation of reliability aspects of wireless communication, such as fading effects, interferences, presence of obstacles and weather conditions in a general and rather easy way. The simulation model was implemented in terms of a class of extended Petri nets to explicitly represent parallelism of events and processes in the WLAN as a distributed system. In the simulation, the behaviour of four fundamental performance metrics packet delivery ratio, average number of hops, relative network traffic and end-to-end delay were investigated with varying distance of transmission and different combinations of model parameters. Copyright (c) 2012 John Wiley & Sons, Ltd.
Keywords: mobile wireless ad hoc networks; oriented links; simulation; extended Petri nets